Small business credit scoring and credit availability - Allen N. Berger; W. Scott Frame (Federal Reserve Bank of Atlanta, 2005)
U.S. commercial banks are increasingly using credit scoring models to underwrite small business credits. This paper discusses this technology, evaluates the research findings on the effects of this technology on small business credit availability, and links these findings to a number of research and public policy issues.
Keywords: G21; G28; G34; L23; 330; banks; credit scoring; small business; Kreditwürdigkeit; KMU; USA